REPRESENTATIVE BODIES OF LOCAL SELF-GOVERNMENT IN UKRAINE: NOMENCLATURE AND CONSTITUTIONAL REGULATION - Hedulianov, Vadim (Scientific Journal of Polonia University, 2023)
Nowadays a lot of attention in Ukraine is given to the activity of the local self-government bodies. The aim of the article is to give the list of the representative bodies of local self-government (municipal bodies) in Ukraine and to propose how the relevant constitutional regulation might be improved. The author uses legal synthesis, legal analysis, deductive, inductive, comparative (historical perspectives – so called ‘vertical’ comparison) and hermeneutical methods; the article researches the issue based on the antropocentrical and axiological methodological approaches The author analyses Ukrainian constitutional developments in the democracy’s regulation, then pays attention to the theoretical aspects of democracy’s classifications. The last part of this article covers the current problems of the representative bodies of local government in Ukraine: namely, their nomenclature. The author argues that the Ukrainian self-organizes bodies of population can’t be recognized as “representative bodies” (despite the adjectives in the name of the analyzed institute of constitutional law and the analyzed group of bodies). But they probably have a public nature – because they are an element of the system of local self-government in Ukraine. The author invites municipalists to the discussion and argues the own directions of the future researches.